IMPLEMENTATION OF UNDERWATER GLIDER AND IDENTIFICATION OF ITS PARAMETERS (Jurnal Teknologi (Sciences & Engineering), 2016)
This paper is part of a series that describe the development and setup of intelligent underwater vehicle. Here we focus on the implementation tests for the identification of the actuating device parameters. An energy efficient type of glider is chosen with its block diagram presented. The assembled model is placed in a mini pool for movement tests with the objective of setting up the motors and pump. When put in neutral, its immersion and surfacing position show that there is interdependent between pump operation time, ballast bag maze, displacement of weight and glider attitude angle. These dependencies are described by linear equations and coefficients which are then identified.